Temporal Processing of Joyful and Disgusting Food Pictures by Women With an Eating Disorder - Gagnon, Caroline; Bégin, Catherine; Laflamme, Vincent; Grondin, Simon (Frontiers in Human Neuroscience, 2018)
The present study used the presentation of food pictures and judgements about their duration to assess the emotions elicited by food in women suffering from an eating disorder (ED). Twenty-three women diagnosed with an ED, namely anorexia (AN) or bulimia nervosa (BN), and 23 healthy controls (HC) completed a temporal bisection task and a duration discrimination task. Intervals were marked with emotionally pre-rated pictures of joyful and disgusting food, and pictures of neutral objects. The results show that, in the bisection task, AN women overestimate the duration of food pictures in comparison to neutral ones. Also, compared to participants with BN, they perceive the duration of joyful food pictures as longer, and tend to overestimate the duration of the disgusting ones. These effects on perceived duration suggest that AN women experience an intense reaction of fear when they are confronted to food pictures. More precisely, by having elevated the arousal level and activated the defensive system, food pictures seem to have speeded up the rhythm of the AN participants’ internal clock, which led to an overestimation of images’ duration. In addition, the results reveal that, in both tasks, ED women present a lower temporal sensitivity than HC, which is related to their ED symptomatology (i.e., BMI, restraint and concern) and, particularly, to their weaker cognitive abilities in terms of attention, processing speed and working memory. Considered all together, the findings of the present experiment highlight the role of fear and anxiety in the manifestations of AN and point out the importance of considering non-temporal factors in the interpretation of time perception performance.